The influence of three photoactivation techniques on the sorption and solubility of different composite resins - Marçal Seitaro MATUMOTO; Márcio José MENDONÇA; Priscilla do Monte Ribeiro BUSATO; Brenda Matsunaga LAURINDO; Veridiana CAMILOTTI
Abstract Introduction There is a growing demand for aesthetic restorations and the polymerized composite resins are the most used material in these procedures. In order to achieve greater resistance to solubilization proper polymerization is required. Objective Evaluate the influence of three photoactivation techniques, on sorption and solubility of three composite resins. Materials and methods 90 test samples measuring 8 mm diameter and 1 mm thick were made and divided into 9 groups (n=10) of resins -Filtek Z350 XT, Tetric N-Ceram and IPS Empress Direct, each of them was polymerized with LED Bluephase, using the techniques: Conventional, Soft-Start (SS) and Pulse Delay (PD). Afterwards they were placed in desiccator with silica gel at 98.6 F and weighed daily until obtaining a constant mass (m1). Then they were immersed in deionized water for seven days and weighed again (m2). The test sample reconditioning was performed using the m1 procedure, until a constant mass (m3 ) was obtained. The sorption and solubility values were calculated and subjected to ANOVA test (two-way), followed by Tukey post hoc, p<0.05. Result There were no statistically significant differences in sorption and solubility among the studied resins when photoactivation techniques were compared. For solubility analysis, statistically significant differences were observed among the materials. The results for composite resin Filtek Z350 XT presented higher statistical hybridization values than those of the other evaluated resins. Conclusion The different forms of photoactivation had no influence on the sorption and solubility of the tested composite resins.